2023
DOI: 10.3389/fpls.2022.1086007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of sucrose and alanine contents in edamame beans

Abstract: The sucrose and Alanine (Ala) content in edamame beans significantly impacts the sweetness flavor of edamame-derived products as an important attribute to consumers’ acceptance. Unlike grain-type soybeans, edamame beans are harvested as fresh beans at the R6 to R7 growth stages when beans are filled 80-90% of the pod capacity. The genetic basis of sucrose and Ala contents in fresh edamame beans may differ from those in dry seeds. To date, there is no report on the genetic basis of sucrose and Ala contents in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…All accessions were planted similarly to Singer et al 2022 and Wang et al 2022 [ 23 , 24 ]. Briefly, a total of 390 soybean accessions from a total of 17 countries from the Southern Core Collection that has been maintained at Virginia Tech were grown in Blacksburg (BB) and Warsaw (W), Virginia, for three years from 2019 to 2021.…”
Section: Methodsmentioning
confidence: 99%
“…All accessions were planted similarly to Singer et al 2022 and Wang et al 2022 [ 23 , 24 ]. Briefly, a total of 390 soybean accessions from a total of 17 countries from the Southern Core Collection that has been maintained at Virginia Tech were grown in Blacksburg (BB) and Warsaw (W), Virginia, for three years from 2019 to 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The sweetness flavor of edamame beans is a crucial factor for consumer acceptance, and it is influenced by the content of sucrose and alanine (Ala). Wang et al (2023) conducted a GWAS of fresh edamame beans of 189 accessions and identified 43 and 25 genetic markers associated with sucrose and Ala content, respectively. Four genes that affect sucrose biosynthesis and 37 novel genes related to sucrose content were identified, along with three genes with likely relevant effects on Ala content and 22 novel Ala-related genes.…”
Section: Food Grade Considerations For Carbohydratesmentioning
confidence: 99%
“…Because the ME of sucrose (3900 kcal•kg −1 ) is significantly greater than that of starch (2918-3396 kcal•kg −1 ), animal producers are interested in feed formulation with higher sucrose concentration (John, 2008;Ostezan et al, 2023). Additionally, higher sucrose concentration is positively correlated with the sweetness of soy-based products, including natto, tofu, edamame, and soymilk (Rosset et al, 2012;Sui et al, 2020;Wang et al, 2023). Thus, improving sucrose content has become more common in soybean breeding programs due to its higher ME efficiency for animal feed and the natural sweetness in soymeal for human consumption (Ficht et al, 2022;Sui et al, 2020).…”
Section: Introduction To Carbohydratesmentioning
confidence: 99%
“…Since the largest soybean meal consumers are non-ruminant animals, developing new soybean cultivars with high sucrose and low RFOs is crucial to improve digestibility and feed efficiency. In addition, increased sucrose content in soybean seeds is also essential to improve the sweet flavor of soy-based products, such as tofu, edamame, and soymilk (Rosset et al, 2012;Sui et al, 2020;Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%